A Marriage of Convenience: the Roman Catholic Church and Modernity in Nineteenth-Century Europe - Janowski, Maciej (Kwartalnik Historyczny, 2018)
The article examines the problem of Dechristianization and secularization in nineteenth-century Europe, with a special emphasis on the Roman Catholic Church’s ways of reacting to modernity. The Church managed to come to terms with modernity and to escape secularization at the price of supporting modern radical nationalism in the early twentieth century.